1997
DOI: 10.1159/000150514
|View full text |Cite
|
Sign up to set email alerts
|

Host-Controlled Cell-to-Cell Movement of a Hybrid Barley Stripe Mosaic Virus Expressing a Dianthovirus Movement Protein

Abstract: The triple gene block (TGB) of barley stripe mosaic virus (BSMV), coding for viral movement proteins (MPs), was replaced by the single MP gene of red clover necrotic mosaic virus (RCNMV). Accumulation of the hybrid virus in barley plants (the selective host for BSMV) was reduced compared to BSMV. The hybrid virus induced small necrotic local lesions on Chenopodium amaranticolor leaves and did not infect Nicotiana clevelandii (te selective host for RCNMV). The hybrid virus accumulated in the inoculated leaves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
0
16
0
5
Order By: Relevance
“…We have shown recently that movement of chimaeric variants of the TGB-containing barley stripe mosaic virus (BSMV) can be potentiated by artificially inserted MP genes of TMV and RCNMV (Solovyev et al, 1996(Solovyev et al, , 1997. To test the CAIA Transient complementation of plant virus movement Transient complementation of plant virus movement specificity of PVX.GUS-Bsp complementation in the transient bombardment assay, we inoculated pPVX.GUS-Bsp with 35S-based plasmids containing the MP genes of tobamoviruses (ToMV or Cr-TMV), a dianthovirus (RCNMV) or a bromovirus (BMV) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown recently that movement of chimaeric variants of the TGB-containing barley stripe mosaic virus (BSMV) can be potentiated by artificially inserted MP genes of TMV and RCNMV (Solovyev et al, 1996(Solovyev et al, , 1997. To test the CAIA Transient complementation of plant virus movement Transient complementation of plant virus movement specificity of PVX.GUS-Bsp complementation in the transient bombardment assay, we inoculated pPVX.GUS-Bsp with 35S-based plasmids containing the MP genes of tobamoviruses (ToMV or Cr-TMV), a dianthovirus (RCNMV) or a bromovirus (BMV) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a modification of this approach, it was shown that MP produced in transgenic plants could complement a transportdeficient virus (Deom et al, 1987 ;Ziegler-Graff et al, 1991 ;Kaplan et al, 1995). In a third type of complementation experiment, a recombinant virus genome was constructed with the wild-type MP gene replaced by the MP gene from a heterologous virus (Ziegler-Graff et al, 1991 ;Nejidat et al, 1991 ;De Jong & Ahlquist, 1992 ;Giesman-Cookmeyer et al, 1995 ;Solovyev et al, 1996Solovyev et al, , 1997. The ability of the inserted MP gene to facilitate cell-to-cell movement of the hybrid virus provided insights into the functional compatibility of the MPs of different viruses.…”
Section: Introductionmentioning
confidence: 99%
“…These MPs have been shown conclusively to bind RNA in vitro and to increase the size exclusion limit of plasmodesmata in mesophyl cells to allow cell-to-cell movement (19). Moreover, both TMV MP and RCNMV MP have been shown to complement the transport of other plant viruses belonging to different taxonomic groups, such as barley stripe mosaic virus (20,21), potato virus X (22), and brome mosaic virus (23).…”
mentioning
confidence: 99%
“…This follows from earlier data on complementation of virus transport in double infections in plants (reviewed by Atabekov & Taliansky, 1990), as well as from more recent experiments with transgenic plants expressing viral MPs (Ziegler-Graf et al, 1991 ;GiesmanCookmeyer et al, 1995 ;Kaplan et al, 1995), hybrid viruses engineered from infectious cDNA clones (De Jong & Ahlquist, 1992 ;Giesman-Cookmeyer et al, 1995 ;Solovyev et al, 1996Solovyev et al, , 1997, and co-expression of a transport-deficient virus and an unrelated MP gene inoculated as 35S promoter plasmids . We have reasoned that the latter two approaches could be used as fast experimental means to test the activity of a protein suspected to be involved in virus cellto-cell transport.…”
Section: Discussionmentioning
confidence: 82%
“…It has been found previously that the infectious cDNA clone of BSMV RNAβ, in which heterologous plant virus MPs are inserted as cassettes, may be used to study the compatibility between the virus-coded transport functions in their common hosts (Solovyev et al, 1996(Solovyev et al, , 1997. C. amaranticolor and C. quinoa used for mechanical inoculation with the BSMV\BYV RNAβ hybrids are susceptible to both parental viruses (Duffus, 1973 ;Atabekov & Novikov, 1989).…”
Section: Bsmv Chimeras With Tgb Replaced By the Byv P65 Are Competentmentioning
confidence: 99%